Consumers Consumption Values and Consumer Satisfaction toward Continuous Intention to View Digital Video Content - Kamalul Ariffin, Shaizatulaqma; Hilmawan, Hadi; Zhang, Qi (Journal of Entrepreneurship, Business and Economics; Vol 11 No 2 (2023), 2023)
Digital video content has growing into a global business phenomenon during last few years, the prosperity and success of digital video contents heavily relies on the continuance usage of consumers. This study aims to examine the relationship between consumer consumption values and consumer satisfaction towards continuous intention to watch digital content. We collected quantitative data via an online survey disseminated to a total of 215 respondents among young digital video consumers in Malaysia, and the data was analyzed using SPSS/PLS-SEM. The findings revealed that the functional value, entertainment value, perceived usefulness, and confirmation were significant determinants of consumer satisfaction. Meanwhile, social value and informative value were found to be insignificant to consumer satisfaction and social media usage was found to not strengthen the relationship between consumer satisfaction and continuous intention. The findings could help video content providers to understand consumers’ preferences as well as marketers and organizations to use and adapt these factors in their marketing strategies to improve video content creation so it can be more effective and attractive to consumers’ needs and preferences. This is one of the few studies that implied social media usage as a moderator towards continuous intention to view video content with the integration of two theories that were Theory of Consumption Value and the Expectation of Confirmation Model. Research paper Keywords: Satisfaction; Continuous Intention; Social Media Usage; Theory of Consumption Values; Expectation Confirmation Model Reference to this paper should be made as follows: Ariffin, S. K., Hilmawan, H., & Zhang, Q. (2023). Consumers Consumption Values and Consumer Satisfaction toward Continuous Intention to View Digital Video Content. Journal of Entrepreneurship, Business and Economics , 11 (2), 81–129.